Efficient methods for estimating quantal-response relationships with specific emphasis on the sensitivity testing of explosive devices - Van Wijck,Willie,1953- (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.)(Ing.) -- University of Stellenbosch, 1989.